Non-Surgical Treatment of Colonic Diverticulitis (a Review) - Sh. V. Timerbulatov; E. N. Gainullina; M. V. Timerbulatov (Креативная хирургия и онкология, 2020)
Colonic diverticulitis poses an adverse medical and social problem for its prevalence, variety of clinical manifestations and complications and is becoming menacing as the people’s life expectancy reaches beyond 80 years. Many of the traditional principles no longer apply. This situation warrants an earlier diagnosis of colonic diverticulitis, its adequate treatment and prevention. The article presents a review of current literature on the conservative treatment of inflammatory colonic diverticulitis. The past 20 years have witnessed a noticeable increase to 20 % of hospitalisation rate with complicated diverticulitis and a higher associated financial burden. We discuss issues in the diagnosis and criteria for diverticulitis severity assessment with laboratory, biochemical data and radiation imaging (computer tomography, magnetic resonance imaging, ultrasound, colonoscopy). A critical overview is provided on anti-inflammatory and antibiotic drug usage in recurrence prevention and treatment of acute and recurrent diverticulitis, aside to recommendations in outpatient care. Despite a manifold of clinical studies and guidelines available, the adequate choice of drugs, dosages and duration of treatment remains an open challenge.